Assessment of splanchnic perfusion with gastric tonometry in the immediate postoperative period of cardiac surgery in children - Souza,Renato Lopes de (2001)
OBJECTIVE - A prospective, nonrandomized clinical study to assess splanchnic perfusion based on intramucosal pH in the postoperative period of cardiac surgery and to check the evolution of patients during hospitalization. METHODS - We studied 10 children, during the immediate postoperative period after elective cardiac surgery. Sequential intramucosal pH measurements were taken, without dobutamine (T0) and with 5mcg/kg/min (T1) and 10 (T2) mcg/kg/min. In the pediatric intensive care unit, intramucosal pH measurements were made on admission and 4, 8, 12, and 24 hours thereafter. RESULTS - The patients had an increase in intramucosal pH values with dobutamine 10mcg/kg/min [7.19± 0.09 (T0), 7.16±0.13(T1), and 7.32±0.16(T2)], (p=0.103). During the hospitalization period, the intramucosal pH values were the following: 7.20±0.13 (upon admission), 7.27±0.16 (after 4 hours), 7.26±0.07 (after 8 hours), 7.32±0.12 (after 12 hours), and 7.38±0.08 (after 24 hours), (p=0.045). No deaths occurred, and none of the patients developed multiple organ and systems dysfunction. CONCLUSION - An increase in and normalization of intramucosal pH was observed after dobutamine use. Measurement of intramucosal pH is a type of monitoring that is easy to perform and free of complications in children during the postoperative period of cardiac surgery.